PKM Kewirausahaan “KEBAB PICUUY” Bagi Ibu Rumah Tangga di Kecamatan Manggala - Mustari Mustari; Nur Arisah; Nurjannah Nurjannah; Ratnah S; Sitti Hajerah Hasyim (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
One of the activities that can increase the entrepreneurial spirit for the community is through a home industry business or commonly called a home business in making "KEBAB PICUUY" with the main filling of banana and chocolate wrapped in kebab skin. The methods used in this activity include lectures, questions and answers or discussions, and training. The results obtained are (1) The training on making "KEBAB PICUUY" was responded well by the participants; (2) The high interest and motivation of the training participants greatly supports the transfer of knowledge and skills from the servants to the training participants, so that the training materials provided can be absorbed by all; and (3) The training products for making "KEBAB PICUUY" can be consumed daily and can be used as entrepreneurial products.